MicroRNA-1 Inhibits the Growth of Breast Cancer Cells MDA-MB-231 and MCF-7 Treated with Hydatid Cyst Fluid - Hadis Jafari; Mahmoud Mahami-Oskouei; Adel Spotin; Behzad Baradaran; Dariush Shanehbandi; Amir Baghbanzadeh; Zahra Alizadeh (Journal of Tropical Medicine)
Antigens in hydatid cyst fluid (HCF) have been discovered to bear a significant resemblance to antigens present in cancer cells. MicroRNA-1 (miR-1) is a well-known member of the tumor inhibitor miRNA family and has been shown to have pro-apoptotic and tumor-inhibitory functions. This study aimed to evaluate the ability of HCF to prevent breast cancer and to explore the underlying mechanisms that affect cancer cells. For this study, MDA-MB-231 and MCF-7 breast cancer cells were cultured and divided into two groups: one group received HCF treatment and the other group was untreated and served as the control group. The cytotoxicity and cell viability of various HCF concentrations on breast cancer cells were evaluated using the MTT assay. In addition, the expression level of miR-1 in HCF-treated and untreated breast cancer cells was analyzed using qRT-PCR. The study found that HCF treatment reduced the growth of MDA-MB-231 and MCF-7 breast cancer cells, indicating that it was cytotoxic to the cells. Specifically, the IC50 concentration of HCF after 24 hours of treatment was 7.32 µg/mL for MDA-MB-231 cells and 13.63 µg/mL for MCF-7 cells. In addition, qRT-PCR analysis revealed that the expression level of miR-1 was significantly increased in HCF-treated MDA-MB-231 (P=0.0203) and MCF-7 (P=0.0394) cell lines compared to untreated controls. Although HCF has been shown to inhibit the growth of breast cancer cells and to upregulate miR-1, a key tumor suppressor in cancer cells, the specific mechanisms responsible for this effect remain unclear. Further studies are needed to fully understand the molecular pathways underlying HCF’s antitumor activity and its potential as a therapeutic agent in cancer therapy.